Tinto’s explanatory model of the dropout of doctorate students in a Malaysian public university / Yuen Fook Chan ... [et al.] - Chan, Yuen Fook; Supramanian, Kaarthiyainy; Shah Ismail, Izaham; Mohd Ismail, Hamidah; Hassan, Zainudin; Mohd Yusof, Sanitah (Universiti Teknologi MARA, 2023)
The term ‘university dropout’ is widely used to describe the circumstances where students withdraw from their university studies before completion. The purpose of this qualitative study is to discover the factors and experiences that prompt students from the PhD by Research Programmes to end their scholarly journey. A priori factors in the Tinto Model was utilised to investigate the participants’ academic and social integration at university, their achievement potential, study motivation and study condition. Semi-structured interview was employed in this study. Purposive sampling was carried out on a group of eight PhD by Research Program dropouts from a public university in Selangor. Constant comparative method was used to identify the recurring themes and concepts after the qualitative data had been collected. The findings indicated that the participants faced problems with their supervisors that affected their motivation to continue with their PhD study. Personal problems related to finance and health issues further dampened their motivation. Additional issue was lack of support mechanism for the postgraduate students. Furthermore, low study motivation and study conditions added to their determination to quit. These findings can help public universities in Malaysia to develop some relevant policies to address the postgraduate student dropout issues in Malaysia. Hopefully, university authorities could address the critical issues faced by the postgraduate students to overcome the phenomenon of university dropout.